Technology and Crafts in Archaeology: A Critical Review of Archaeological Approaches to Technology - Javad Hoseinzadeh Sadati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“Archaeological Approaches to Technology” by Heather Margaret-Louise Miller, professor at the University of Toronto is truly an updated survey on technology and crafts in archaeology that witnesses the hard efforts of the author. A critical review of the Persian translation of the book will lead us to improve future translations in this area of study. To do this critical review, the author of this paper first read the whole book in a precise way and then made some notes over those parts of the book that were necessary in terms of contents or in editorial aspects. Then to correct some downsides, it was necessary to compare the Persian translation with the original texts, and finally some suggestions have been made for improving the translation. One of the most notable aspects of the book is its wide references over different areas of studies in each section. This could be very useful for graduate students who seek to work on crafts and technology in archaeology. Persian translation of the book has been done in a good way by Vahid Asgarpoor, assistant professor of Art at University of Tabriz, a young and active archaeologist. From the technical point of view, the book is printed and edited in a professional way, the combination of which with its simple translation would probably satisfy the readers. The biggest shortage of the translation is that the translator sticks too much to the main texts and its structure in a way that in some parts of the book the grammar is more like the original language than to Persian.